PENGEMBANGAN ICE BREAKING UNTUK HAFALAN MUFRODATH DI MADRASAH DINIYAH - Fatqu Rois; Himatul Munawaroh; Hanik Shofa Mardiyah (Program Studi Pendidikan Bahasa Arab, 2024)
Teacher teaching vocabulary with speech method. This way can mood of student in classroom bored and ice breaking be a solution. The aim of study is ice breaking imlementation in learning and impact in student memorization. This article use a researce method descriptive qualitative. The result of study is Student more antusiast to learning vocabulary of arabic languange in answreing questions in speaking and writing test. Teacher used Ice Breaking in process learning with give less portion to kinesthetic skill and more giving ice breaking to visual-auditory skill. Impact from ice breaking implementation is making student(santri) more happy in class, increase concentration to learning arabic languange vocabulary and memorization it.